Climate Governance and Agriculture in Southeast Asia: Learning From a Polycentric Approach - Fasting, Siw; Bacudo, Imelda; Damen, Beau; Dinesh, Dhanush (Frontiers in Political Science, 2021)
The global climate governance framework needs to empower wide ranges of groups representing different geopolitical and sector-specific interests to engage in climate action. Learning from polycentric governance approaches provides insight on how to foster inclusive engagement and effective outcomes from global efforts to fight climate change. The Paris Agreement has opened-up room for bottom-up, polycentric governance. The Association of Southeast-Asian Nations Climate Resilience Network (ASEAN-CRN) is an example of an effective polycentric system enhancing resilience and adaption to climate change. The ASEAN Negotiating Group on Agriculture (ANGA) engages the agriculture sector to shape climate governance frameworks. ANGAs case highlights that opening-up space for polycentric systems fosters effective climate action including relevant sectors. Supporting regions to navigate UNFCCC processes enables polycentric systems, increasing resilience and adaptation.